Protein Micropatterning Assay - Quantitative analysis of protein-protein interactions - Sevcsik, Eva (Methods Mol Biol, 2017)
Characterization, especially quantification, of protein interactions in live cells is usually not an easy endeavor. Here, we describe a straightforward method to identify and quantify the interaction of a membrane protein (“bait”) and a fluorescently labeled interaction partner (“prey”) (membrane-bound or cytosolic) in live cells using Total Internal Reflection microscopy. The bait protein is immobilized within patterns in the plasma membrane (e.g. via an antibody); the bait-prey interaction strength can be quantified by determining the prey bulk fluorescence intensity with respect to the bait patterns. This method is particularly suitable also for the analysis of weak, transient interactions that are not easily accessible with other methods.